E-COMMERCE: STUDI TENTANG BELANJA ONLINE DI INDONESIA - Wiwik Rachmarwi (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
The purpose of this research is to know the potential of the e-commerce industry and to establish preliminary assessment, evaluation and understanding of the characteristics of online shopping in Indonesia which experienced the slowest growth in the last five years. Chi-test tests are used to determine the relationship between current online shoppers and demographic variables. The t-test sample is then used to compare the average difference between the current online buyers and the non-online buyers. It also investigates the influence of factors (demographic profile, previous online shopping experience, perceived benefits, consumer lifestyles, and perceived buyer confidence)